Relationship Between Inflation and Financial Stability: A Case Study of ASEAN Nations - Farida, Gina; Kenedi, Kenedi; Agustini, Anti Wulan (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
Inflation is a key macroeconomic indicator that plays a critical role in shaping the direction and stability of financial systems, especially in the ASEAN region, where countries exhibit diverse levels of economic development. Persistent inflationary pressures may lead to systemic risks in the financial sector through rising non-performing loans and declining investor confidence. This study investigates the impact of inflation on financial stability in ASEAN countries, while controlling for exchange rate fluctuations. Utilizing annual panel data from 2000 to 2021, the study employs the Panel Autoregressive Distributed Lag (Panel ARDL) approach. Financial stability is proxied by the banking sector’s Z-score index, with inflation as the primary independent variable and the exchange rate included as a control variable. Prior to estimation, panel unit root, cross-sectional dependence, and cointegration tests are conducted to ensure model robustness. The long-run estimation results show that inflation has a significant negative effect on financial stability (coefficient = -0.206173, p = 0.0256), while the exchange rate is insignificant (p = 0.7967). In the short run, inflation exhibits a temporary positive effect (coefficient = 0.118962, p = 0.0784), whereas the exchange rate remains insignificant. The error correction term (ECT) is negative and significant (coefficient = -0.616539, p = 0.0190), indicating that 61.65% of short-term disequilibrium is corrected toward long-run equilibrium within one period. These findings underscore the critical importance of inflation control as a strategic policy tool to preserve long-term financial stability in ASEAN, alongside consistent macroprudential measures to mitigate external shocks, including exchange rate volatility.